A vision on a methodology for the application of an Intrusion Detection System for satellites - Gios, Sebastien; Van Ouytsel, Charles-Henry Bertrand; Caribe, Mark Diamantino; Legay, Axel (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
The security of satellites has become critical in recent years due to their important role in modern society. However, numerous challenges, including limited computing resources, evolving cyber threats, and the isolated nature of satellites, hinder the development of effective security solutions. Different solutions should be implemented and combined to protect space assets: encryption, access control, zero-trust architecture, etc. This vision presents the challenges and aspects to consider for implementing an Intrusion Detection System (IDS) tailored to improve the security of satellite systems. Our approach uses a multi-level structure to define rule-based and machine-learning security approaches that address the challenges associated with different mission types. By strategically placing IDS components and considering the trade-offs of each location, we improve detection reliability. Additionally, we present an ontology-based method for visualizing the IDS configuration, which provides clear insight into system capabilities, enhances situational awareness, and facilitates identification and response to potential threats. We also provide strategies for updating the IDS while maintaining efficiency and security. This vision helps improve the cybersecurity measures of satellite operations and increase their resilience to cyberattacks.